Educational Innovation for Industry 5.0 in Japan - Ayaka Nakamura (CV Edujavare Publishing, 2026)
Educational innovation for Industry 5.0 has emerged as a strategic imperative in Japan, reflecting the nation's ambition to transition from an information society to a human-centred society that balances economic advancement with the resolution of social problems through the integration of cyberspace and physical space. This study examines the implementation, evolution, and outcomes of educational reforms aligned with Japan's Society 5.0 vision, drawing upon national policy frameworks, the GIGA School Initiative, and empirical evidence from higher education digital transformation. Japan's approach is distinguished by the Society 5.0 concept proposed in the 5th Science and Technology Basic Plan, the GIGA School Initiative achieving one device per student for approximately 13 million learners, the integration of artificial intelligence and data science across all education levels, and the emphasis on Future Skills development including higher-order thinking and cross-cultural competencies. The research identifies four critical dimensions: the Society 5.0 vision as a backcasting framework for curriculum design, the GIGA School infrastructure as a foundation for personalised learning, the transformation of higher education through digital transformation and micro-credentialing, and the persistent tension between technological innovation and socio-cultural conservatism. Findings indicate that Japan has achieved remarkable infrastructure deployment and policy coherence, yet significant challenges remain, including a projected shortage of 789,000 IT talents by 2030, low female participation in science courses at only 7%, teacher readiness gaps with only 28% feeling well-prepared for ICT integration, and the rapid reversion to face-to-face instruction post-pandemic. The study concludes that Japan's model offers valuable insights for nations seeking to align education with Industry 5.0 through systemic digital transformation, while highlighting the necessity of addressing human resource development, gender equity, and pedagogical innovation beyond infrastructure provision.